Inducers of the phenobarbital type (a review); Pharmaceutical Chemistry Journal; Vol. 29, iss. 3 - Bakibaev A. A. Abdigali Abdimanapovich; Novozheeva T. P.; Akhmedzhanov R. R. Rafik Raviljevich; Saratikov A. S. (1995, 1995)
Title screen